2005
DOI: 10.1177/0092070304270729
|View full text |Cite
|
Sign up to set email alerts
|

Contractual Governance, Relational Governance, and the Performance of Interfirm Service Exchanges: The Influence of Boundary-Spanner Closeness

Abstract: Academics and managers are confronted with reconciling the social and economic aspects of business-to-business exchanges. In a service context, the authors investigate the relative importance of contractual and relational governance on exchange performance and the influence of the boundary spanner on the implementation of these governance mechanisms and on exchange performance. They test a model of the governance of commercial banking exchanges using interview data with both parties to the exchange (the accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
259
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(281 citation statements)
references
References 77 publications
9
259
0
13
Order By: Relevance
“…For example, Burchell and Wilkinson (1997) have highlighted the complementary nature of formal contracts and interfirm social cooperation in the two industrial sectors of mining machinery and kitchen furniture in Britain, Germany and Italy. Ferguson et al (2005) found out that there appear to be sufficient relational norms that mitigate any substantial negative effect of contractual governance in commercial banking exchanges in North America. Taking the research of the Chinese context as an example, our finding is also consistent with Yeung's (2006) observation that ethnic Chinese businesses in Southeast Asia employ both social networks and more formal (bureaucratic) forms of firm control.…”
Section: Relational Governance and Contractual Governance Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Burchell and Wilkinson (1997) have highlighted the complementary nature of formal contracts and interfirm social cooperation in the two industrial sectors of mining machinery and kitchen furniture in Britain, Germany and Italy. Ferguson et al (2005) found out that there appear to be sufficient relational norms that mitigate any substantial negative effect of contractual governance in commercial banking exchanges in North America. Taking the research of the Chinese context as an example, our finding is also consistent with Yeung's (2006) observation that ethnic Chinese businesses in Southeast Asia employ both social networks and more formal (bureaucratic) forms of firm control.…”
Section: Relational Governance and Contractual Governance Mechanismsmentioning
confidence: 99%
“…Moreover, RET describes a set of relational contracting norms, which are adaptations of the norms common to all contracts (MacNeil, 2000). Evidently, the popular and legal notion of contract is more compatible to the concept of contract in TCE than in RET (Ferguson et aL, 2005). To distinguish between TCE and RET approaches to contract, researchers have referred to contracts as hard and soft, explicit and normative, formal and informal, and written and unwritten (Antia and Frazier, 2001;Lusch and Brown, 1996).…”
Section: Relational Exchange Theory Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Transaction cost economics (Williamson, 1979) and relational exchanges (Macneil, 1980) are the two mainstream theoretical perspectives that capture those intermediate modes of governance, which are often expressed on a transactional-relational continuum. Although these transactional and relational terms are typical, the dual mechanism is also referred as hard and soft, explicit and normative, formal and informal or written and unwritten contracts by researchers (Ferguson et al, 2005). Thus, contractual governance (or hard, explicit, formal, and written contracts) reflects the formalization of the inter-firm exchanges and relational governance (or soft, normative, informal, and unwritten contracts) signifies the social norms that regulate the relationship.…”
Section: Inter-firm Governance and Relationship Qualitymentioning
confidence: 99%
“…A formal approach relies on legal artifacts such as contracts [Ferguson et al, 2005] or on intellectual property rights to convey the roles and responsibilities of network partners. A similar level of agreement can be seen at a more operational level (e.g.…”
mentioning
confidence: 99%